Non-canonical interactions of the β subunit of the translation elongation complex eEF1B and analysis of their possible functional role - Kapustian, L.M.; Dadlez, M.; Negrutskii, B.S. (Вiopolymers and Cell, 2016)
Aim. To predict protein networks which may comprise the β subunit of the translation elongation complex eEF1B in lung carcinoma cell line. Methods. The protein partners of eEF1Bβ from cytoplasmic extract of A549 cells were identified by co-immunoprecipitation (co-IP) combined with liquid chromatography-tandem mass spectrometry (LC-MS/MS). The molecular interaction network for eEF1Bβ was predicted and visualized by a Cytoscape 3.2.0 program using an MCODE plugin. GO analysis of cellular distribution was performed by a STRAP Program. Results. 162 high-scored proteins interacting with eEF1Bβ in the cytoplasm of lung carcinoma cells A549 have been identified by mass-spectrometry. Possible functional networks involving these contacts were predicted bioinformatically. Conclusions. Four protein networks are identified as possible targets of eEF1Bβ in lung cancer cells. These groups are involved in the cell cycle regulation; DNA replication and repair; chromatin remodeling; chaperoning and signal transduction. The dataallow to narrow down further search for non-canonical cancer-related function of eEF1Bβ.